Haemodynamic Effect of Coronary Angulations on Subsequent Development of Coronary Artery Disease: A Preliminary Study - Chachaina, T.; Sun, Zhonghua; Jewkes, James (IEEE Computer Society, 2010)
The aim of this study is to investigate the hemodynamic effect of the angulations in the left coronary bifurcation on subsequent development of coronary artery disease. Eight 3D left coronary artery models were generated based on the anatomical details and simulated for numerical analysis. The angulations at the left coronary bifurcation were simulated with angles ranging from 120°, 105°, 90°, 75°, 60°, 45°, 30° to 15°. Computational fluid dynamic models were produced for analysis of flow velocity, wall pressure and wall shear stress. Our results showed that wide angled models produced low wall shear stress and high wall pressure at the left coronary bifurcation regions, whereas, flow pattern was more smooth and laminar with narrow angled models than those with wide angle models. Our analysis indicates the flow-field correlation between coronary angulation and development of atherosclerosis. Future studies are required to analyse the realistic coronary models from patients' data with different degree of coronary stenosis.